The Role of Transformational Leadership in Enhancing Employee Commitment and Loyalty in The Private Sector in Riyadh Province (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to explore the role of transformational leadership in enhancing commitment and loyalty among employees in the private sector in Riyadh Province. Transformational leadership is considered a style of leadership that relies on building strong and sustainable relationships between leaders and followers, encouraging participation in decision-making, and fostering innovation and creativity. Riyadh Province, with its diverse array of companies and institutions across various sectors, provides an ideal environment for investigating this topic. The research methodology includes a review of literature related to transformational leadership and its impact on employee commitment and loyalty, as well as data collection through surveys distributed to a random group of employees in several private companies in Riyadh Province. The data were analyzed using advanced statistical methods to understand the relationship between transformational leadership variables and the level of commitment and loyalty among employees. The results of the study indicate that transformational leadership plays a crucial role in enhancing employee commitment and loyalty in the private sector in Riyadh Province. The study also shows that key factors contributing to the success of implementing transformational leadership include supportive organizational culture and strong managerial direction. Based on these findings, the study provides practical recommendations for leaders and managers in the private sector in Riyadh Province on how to enhance transformational leadership and use it effectively to achieve organizational goals and enhance employee satisfaction and loyalty. Thus, the study contributes to a deeper understanding of the role of transformational leadership in improving performance and enhancing commitment and loyalty among employees in the private sector in Riyadh Province, and provides a practical framework for achieving this in the current work environment.
Keywords: Transformational Leadership; Employees Commitment; Employees Loyalty; Private Sector